Батяня. Комбату лишнего не надо: [повесть] / Сергей Зверев - Зверев Сергей Иванович (Спецназ ВДВ, 2006)
Экземпляры: ф. 12 (20160127) / Инвентарный номер: 51149 / Цена: 50.00 / Авт.знак: З-43 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6